Research hotspots and trends in immunotherapy for cholangiocarcinoma: a bibliometric analysis (2014-2023) - Qu, Xilin; Wang, Qian; Zhu, Fengfeng; Liang, Hao; Long, Zhangtao; Wu, Yachen; Jiang, Mengliang; Liu, Zhaohai; Dai, Xiaoming; Zhu, Zhu (Frontiers in Immunology, 2024)
BackgroundCholangiocarcinoma (CCA) is a malignant tumor of the gastrointestinal tract with a poor prognosis. Immunotherapy plays an important role in the treatment of CCA. This study aimed to investigate the research hotspots and trends in immunotherapy for CCA.MethodsThe Web of Science Core Collection was searched for literature related to CCA immunotherapy research from January 1, 2014, to December 31, 2023, and features such as country, institution, authors, references, and keywords in the included literature were quantitatively and visually analyzed using the VOS viewer and CiteSpace software.ResultsA total of 252 English publications published between 2014 and 2023 were included. The publications were mainly from China and the United States, with Fudan University being the institution that published the most papers. The highest number of publications came from Frontiers in Oncology. The most prolific authors were Jia Fan, Jian Zhou from China and Pa-Thai Yenchitsomanus from Thailand, while the Journal of Clinical Oncology ranked first in the number of citations among the co-cited journals. In recent years, the focus of research has shifted from “immune checkpoint” and “chemotherapy” to “immunotherapy combined therapy.” Currently, the research frontiers are “microenvironment,” “immune cells,” and “macrophages.”ConclusionOur study analyzes the research hotspots and trends in CCA to provide a knowledge map of immunotherapy research, which will serve as a reference and direction for future research.